Zirconium-based amorphous alloy material, preparation method, rotating shaft assembly and electronic equipment
By adding Nb element to Zr-Cu-Al-Ni alloy and adjusting the composition, a zirconium-based amorphous alloy material with high tensile fracture strength and Vickers hardness was prepared, which solved the problems of existing materials in terms of tensile mechanical properties. insufficient.
Patent Information
- Application Number
- CN202310910829.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
Existing zirconium-based amorphous alloy materials perform poorly in tensile mechanical properties and cannot meet the needs of higher strength and toughness.
By adding Nb element on the basis of Zr-Cu-Al-Ni alloy and adjusting the content of each component, a zirconium-based amorphous alloy material composed of ZraCubAlcNidNbe was prepared to improve its glass-forming ability and tensile fracture strength.
The high tensile breaking strength and Vickers hardness of zirconium-based amorphous alloy materials have been achieved, with the tensile breaking strength reaching over 1.8GPa and the Vickers hardness reaching over 520HV, meeting higher strength and toughness requirements.
Smart Images

Figure CN119332181A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of amorphous alloy materials, and in particular to zirconium-based amorphous alloy materials, preparation methods, shaft assemblies and electronic equipment. Background Art
[0002] In recent years, electronic devices have become an important part of people's lives. With the increasing demand for electronic devices, various forms of electronic products have emerged. Among them, the requirements for electronic device components are also getting higher and higher, such as the hinges in folding mobile phones and the keels of protective cases. As an important raw material for these components, the performance of amorphous alloy materials plays a vital role in the product.
[0003] Amorphous alloys are metal alloys that retain the disordered atomic structure of the liquid in the solid state by cooling the alloy melt at a high rate so that the atoms in the alloy melt do not have time to arrange in order. Amorphous matter is a complex multi-body interaction system, and its basic characteristics are: complex atomic and electronic structure, long-range disorder of microstructure, the system is energetically metastable, and has complex multiple relaxation behaviors. In addition, its physical, chemical and mechanical properties, characteristics and structure evolve over time. Amorphous alloys have excellent properties such as high elasticity and high hardness, especially iron-based and zirconium-based amorphous alloy materials. Zirconium-based amorphous alloys have strong amorphous forming ability and a wide supercooled liquid phase region. They can be easily prepared into high-quality bulk amorphous with less complex equipment, and at the same time show excellent mechanical properties.
[0004] Although many zirconium-based alloys have been developed and have high compressive strength, their tensile mechanical properties are poor, which restricts the application of amorphous alloys. Summary of the invention
[0005] In view of this, the present application provides a zirconium-based amorphous alloy material, a preparation method, a shaft assembly and an electronic device to solve the problem that the existing zirconium-based amorphous alloy materials cannot meet the requirements of higher strength and toughness.
[0006] Some embodiments of the present application provide a zirconium-based amorphous alloy material. The present application is introduced from multiple aspects below, and the embodiments and beneficial effects of the following multiple aspects can be referenced to each other.
[0007] In a first aspect, the present application provides a zirconium-based amorphous alloy material, the composition of the zirconium-based amorphous alloy material is: Zr a Cu b Al c Ni d Nb e, where a, b, c, d, and e are percentages of the number of atoms, and the percentages of the number of atoms are: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100.
[0008] According to the zirconium-based amorphous alloy material of the embodiment of the present application, Nb is added to the composition of the Zr-Cu-Al-Ni alloy, and the content of each component is adjusted. The amorphous alloy material with this component content not only has good glass-forming ability, but also has high tensile fracture strength.
[0009] As an embodiment of the first aspect, the percentage of each atomic number is: 46≤a≤49, 30≤b≤33, 9≤c≤11, 6≤d≤10, 0.5≤e≤5. This component content has higher tensile properties.
[0010] As an embodiment of the first aspect, the composition of the zirconium-based amorphous alloy material is: Zr 48 Cu 32 Al 10 Ni7Nb3、Zr 48 Cu 32 Al 10 Ni9Nb1 or Zr 53 Cu 20 Al 15 Ni 10 Nb2. The content of this component can effectively improve the tensile properties of the material.
[0011] As an embodiment of the first aspect, the critical forming size of the zirconium-based amorphous alloy is not less than 6 mm. This size may indicate that the alloy material is an amorphous alloy material.
[0012] As an embodiment of the first aspect, the tensile fracture strength of the zirconium-based amorphous alloy material is ≥1.8 GPa, and the Vickers hardness is ≥520 HV. The tensile fracture strength is much greater than the tensile fracture strength of amorphous alloy materials prepared from other substrates in the application. The strong bending resistance is conducive to extending the overall life of the electronic equipment containing it.
[0013] In a second aspect, the present application also discloses a method for preparing a zirconium-based amorphous alloy material, comprising the following steps:
[0014] According to the composition of ZraCubAlcNidNbe, the required metal raw materials Zr, Cu, Ni, Al and Nb are weighed, wherein a, b, c, d and e are atomic percentages, and the percentage of each atom is: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100;
[0015] All raw materials are smelted to obtain a master alloy ingot;
[0016] The master alloy ingot is remelted and cast to obtain a zirconium-based amorphous alloy material.
[0017] The preparation method of the zirconium-based amorphous alloy material in the embodiment of the present application can obtain an amorphous alloy material with a tensile fracture strength of more than 1.8 GPa and a Vickers hardness of more than 520 HV, and the alloy material can be mass-produced by smelting to meet market demand.
[0018] As an embodiment of the second aspect, all raw materials are smelted to obtain a master alloy ingot, comprising:
[0019] All raw materials are placed in a vacuum arc melting furnace and melted under argon protection to obtain a master alloy ingot. This method can quickly melt and obtain a master alloy ingot with less impurities.
[0020] As an embodiment of the second aspect, metal raw materials Nb, Zr, Ni, Cu, and Al are stacked in a vacuum arc melting furnace in descending order of melting point, and then argon gas is introduced for melting to obtain a master alloy ingot. This step facilitates the full melting of the raw materials.
[0021] As an embodiment of the second aspect, in the step of preparing the master alloy ingot, the smelting conditions are: the smelting temperature is 1200-1500° C., and the smelting time is 2-4 minutes each time. The smelting conditions can fully melt the raw materials.
[0022] As an embodiment of the second aspect, the master alloy ingot is refined at least four times to ensure sufficient melting of the five metals.
[0023] As an embodiment of the second aspect, the mold used in the pouring is a water-cooled copper mold.
[0024] As an embodiment of the second aspect, in the pouring process parameters, the vacuum degree is 10 -3 ~10 -2 Pa, temperature is 800~1400℃, cooling rate is 10~10 2 K / s. The use of low vacuum can ensure that less oxygen enters the alloy, ensuring the alloy performance, and this parameter combination can obtain a purer amorphous alloy with less oxygen content and less inclusions.
[0025] In a third aspect, the present application further discloses a shaft assembly, which is made of the zirconium-based amorphous alloy material as in the embodiment of the first aspect, or the zirconium-based amorphous alloy material obtained by the preparation method of the embodiment of the second aspect.
[0026] In a fourth aspect, an embodiment of the present application further discloses an electronic device, comprising the zirconium-based amorphous alloy material as in the embodiment of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The bending test diagram of the rotating shaft made of amorphous alloy materials in some schemes;
[0028] Figure 2 This is a test diagram of the yield condition of the shell keel made of amorphous alloy material in another scheme after being hit by a virtual arm at a closed angle drop of 45° (1m);
[0029] Figure 3 This is a schematic diagram of the structure of a foldable screen mobile phone according to an embodiment of the present application;
[0030] Figure 4 A flow chart of a method for preparing a zirconium-based non-alloy material according to an embodiment of the present application;
[0031] Figure 5 This is the X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 1 of the present invention;
[0032] Figure 6 This is the curve of the 6 mm alloy round bar obtained by copper mold casting in Example 1 of the present invention when stretched;
[0033] Figure 7 The transmission and energy spectrum images of the 6 mm alloy round rod cast by copper mold in Example 1 of the present invention;
[0034] Figure 8 This is the X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 2 of the present invention;
[0035] Fig. 9 This is the curve of the 6 mm alloy round rod obtained by copper mold casting in Example 2 of the present invention when stretched;
[0036] Fig.10 This is the X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 3 of the present invention;
[0037] Fig.11 This is the curve of the 6 mm alloy round bar obtained by copper mold casting in Example 3 of the present invention when stretched;
[0038] Fig.12 This is the X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 4 of the present invention;
[0039] Fig.13 This is the curve of the 6 mm alloy round bar obtained by copper mold casting in Example 4 of the present invention when stretched;
[0040] Fig.14This is the X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 5 of the present invention;
[0041] Fig.15 This is the curve of the 6 mm alloy round rod cast by copper mold in Example 5 of the present invention when stretched. DETAILED DESCRIPTION
[0042] The following will provide a clear and complete description of the various embodiments of the present application in conjunction with the accompanying drawings.
[0043] The technical problem of this application is first described below.
[0044] refer to Figure 1 , Figure 1 The bending test diagram of the rotating shaft made of amorphous alloy materials in some schemes is shown. Figure 1 (a)~ Figure 1 As shown in (d) in Figure 1 The amorphous alloy material shown has low fracture strength and poor bending resistance. When the shaft bends, other parts connected to it will also be deformed. Figure 1 For example, when the maximum bending value of the shaft is 2.049E-01, other parts or components of the part with the largest bending value also have different degrees of bending, for example, 1.601E-01, 2.563E-02, etc. For example, Figure 1 (b) to (d) in the figure also bend with the shaft, causing other components to be severely deformed, thereby affecting the overall quality of the product and failing to meet user needs.
[0045] refer to Figure 2 , Figure 2 The following is a test diagram showing the yield condition of a shell keel made of amorphous alloy material in another solution after being hit by a virtual arm at a closing angle of 45° (1m). Figure 2 As shown in (a) and (b), the shell is made of amorphous alloy material with a tensile fracture strength of 1300MPa. During the test, when the closing angle was 45° (1m), a virtual arm impact was performed. After the side wall of the shell keel was impacted by the virtual arm, the local yield phenomenon of the side wall of the keel was serious, that is, the low tensile fracture strength is prone to serious yield phenomenon.
[0046] Analysis of the above Figure 1 and Figure 2 The problem is that the density of existing amorphous alloy products is generally 6.6-6.8g / cm 3 The products prepared under vacuum die-casting conditions usually have a fracture strength of about 1300 MPa and poor bending resistance.
[0047] For example, in some schemes, a non-alloy material product is die-casted by a bedroom die-casting machine. In the mold closing stage, a die-casting machine is used to die-cast amorphous alloys to obtain products. The die-casting machine includes a movable mold, a fixed mold and a die-casting punch. Among them, a cavity is provided between the movable mold and the fixed mold, and a pressure chamber for containing molten metal is provided inside the die-casting punch. As the die-casting punch is pushed forward, the molten metal is poured into the cavity, and then the mold is die-cast on the material. After die-casting, a product of the corresponding shape is obtained, and the product is taken out after the mold is opened.
[0048] In other examples, products can also be obtained by full vertical die casting. The method of obtaining products by equipment die casting can only improve the performance of the product by improving the die casting equipment itself or adjusting the process parameters, but the entire process of die casting is roughly the same, for example, including three main processes of casting mold, die casting and mold opening, and there is little room for improving product performance. For the specific process of die casting in this application, please refer to the description of the prior art, and no detailed description will be given here.
[0049] In the die-casting method described above, the die-casting of zirconium (Zr)-based amorphous alloy materials is used as an example to illustrate the product. Among them, the Zr-based amorphous alloy material is mainly composed of metal elements such as Zr-Cu-Ni-Al, and the alloy density is 6.8g / cm 3 The fracture strength is about 1300MPa under vacuum die-casting conditions. These amorphous die-cast products are mainly used in electronic consumer products, such as complex structural parts such as mobile phone shafts and card slots, and automotive parts such as lock covers. However, the market has a strong demand for lightweighting of these products, but the current die-cast amorphous alloys are still limited in application due to their high strength and low strength of strong steel (yield strength above 2GPa). Therefore, both materials and preparation processes need to be improved.
[0050] The above embodiments are described using Zr-based amorphous alloy materials as an example, and other amorphous materials may also be included in other embodiments. For example, palladium (Pd)-based amorphous system, the tensile fracture strength of this material can reach 1.47GPa, Vickers hardness 4.88GPa, and elastic modulus 91GPa. Magnesium (Mg)-based amorphous system, the biggest disadvantage of Mg-based amorphous system is brittleness, the amorphous size reaches 25mm, the compression strength can reach 880MPa, the tensile fracture strength is about 330MPa, the Vickers hardness is 2.6GPa, the elastic modulus is 39Gpa, and the elongation at break is 1.5%. Rare earth-based amorphous system, neodymium (Nd)-based and praseodymium (Pr)-based amorphous have higher hard magnetic properties, cerium (Ce)-based amorphous has an extremely low elastic modulus, the overall elastic modulus is about 47GPa, the tensile fracture strength is about 18GPa, and the impact toughness can reach 30.4KJ / m 2. However, the disadvantage of rare earth-based amorphous system is that it is not corrosion-resistant and oxidizes quickly in the air. Titanium (Ti)-based amorphous system has a tensile fracture strength of about 1.5GPa, an elastic modulus of about 77.4GPa, an elongation at break of about 1.7%, and a Vickers hardness of 5.5GPa. Iron (Fe)-based amorphous system: has superparamagnetism, a tensile fracture strength of 3.8GPa, an elastic modulus of 210GPa, a Vickers hardness of 12.5GPa, and an elongation at break of 1.6%.
[0051] The above-mentioned amorphous materials can be mass-produced by die-casting. Due to the production method of die-casting, there are certain limitations on the density and tensile fracture strength of the products, and it cannot meet the demand for higher tensile fracture strength. In addition, since the melting points of these substrates are high and higher than the melting points of the smelting molds, such as steel molds. Therefore, mass production cannot be achieved by smelting. The current zirconium-based amorphous system can be mass-produced as a bulk material by smelting. However, the existing zirconium-based amorphous alloy materials have low tensile fracture strength and cannot meet the needs of users.
[0052] In order to solve the above technical problems, an embodiment of the present application provides a zirconium-based amorphous alloy material, which has high tensile fracture strength, can be mass-produced, is convenient for industrial production, and has good application prospects.
[0053] The zirconium-based amorphous alloy material according to the embodiment of the present application and the application of the alloy steel material are described below in conjunction with the accompanying drawings.
[0054] According to a zirconium-based amorphous alloy material provided in an embodiment of the present application, the zirconium-based amorphous alloy with an amorphous structure can be obtained by arc melting, copper mold casting, and conventional component die-casting to obtain an amorphous bulk material or component with an amorphous structure. The zirconium-based amorphous alloy material contains multiple elements of zirconium (Zr), copper (Cu), aluminum (Al), nickel (Ni) and niobium (Nb), that is, the alloy system of the zirconium-based amorphous alloy material is a Zr-Cu-Ni-Al-Nb alloy. Among them, the atomic percentage (percentage of the number of atoms) of each element in the final amorphous alloy conforms to the following general formula (composition of the zirconium-based amorphous alloy material):
[0055] Zr a Cu b Al c Ni d Nb e (general formula)
[0056] Wherein, a, b, c, d, e are percentages of the number of atoms, and the percentages of the number of atoms are: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100. For example, a can be 42, 45, 48, 50, 53, 55 or 58, etc. b can be 20, 25, 30, 35, 40, 45 or 49, etc. c can be 5, 7, 9, 11, 13 or 15, etc. c can be 5, 7, 9 or 11, etc. e can be 1, 2, 3 or 4, etc.
[0057] The amorphous alloy material of the embodiment of the present application adds Nb on the basis of the Zr-Cu-Al-Ni alloy composition to produce the effect of liquid phase separation. In addition, the content of each component is adjusted in the embodiment of the present application. The amorphous alloy material with this component content not only has good glass forming ability, but also the Zr-based amorphous alloy material has a high tensile fracture strength.
[0058] In addition, the Zr-based amorphous alloy material of the embodiment of the present application is easy to form into a block, for example, an amorphous rod or an amorphous component, and has a good application prospect.
[0059] In some embodiments of the present application, in the zirconium-based amorphous alloy material composition, the atomic percentage of each element may be 46≤a≤49, 30≤b≤33, 9≤c≤11, 6≤d≤10, 0.5≤e≤5. This component content has higher tensile properties.
[0060] In some embodiments of the present application, the composition of the zirconium-based amorphous alloy material may be: Zr 48 Cu 32 Al 10 Ni7Nb3、Zr 48 Cu 32 Al 10 Ni9Nb1 or Zr 53 Cu 20 Al 15 Ni 10 Nb2. This component content has ultra-high tensile strength.
[0061] In some embodiments of the present application, the critical forming size of the zirconium-based amorphous alloy is not less than 6 mm, which can indicate that the alloy material is an amorphous alloy material.
[0062] In some embodiments of the present application, the tensile fracture strength of the zirconium-based amorphous alloy material is ≥1.8GPa, and the Vickers hardness is ≥520HV. The tensile fracture strength is much greater than the tensile fracture strength of amorphous alloy materials prepared from other substrates in the application. The bending resistance is strong, which is conducive to extending the overall life of the electronic equipment containing it. And the alloy material can be mass-produced by smelting, which can meet the needs of the market.
[0063] It should be noted that in some embodiments of the present application, in addition to the above components, other components may be added as needed, for example, rare earth elements or titanium (Ti) may be added, so as to meet the requirements of other material properties on the basis of improving the tensile fracture strength achieved in the above embodiments of the present application. For example, the appropriate addition of trace amounts of rare earth elements may inhibit the crystallization trend, improve the stability of the melt, and enhance the amorphous forming ability of the alloy. In addition, the material's impact toughness, magnetic properties, luminescence and other properties may also be improved.
[0064] The zirconium-based amorphous alloy material of the embodiment of the present application can be applied to electronic devices. For example, the zirconium-based amorphous alloy material can be processed into a shaft assembly, a heat-conducting shaft, etc., and applied to a personal computer (PC). It can also be processed into a folding machine shaft, parts for a heat-conducting shaft of a folding machine, etc., and applied to a folding machine. Or it can be processed into a shaft for a tablet, parts for a heat-conducting shaft for a tablet, and applied to a tablet, etc. Taking the folding screen mobile phone in a folding machine as an example, it can be used as a shaft assembly for realizing the unfolding or folding of two screens. The shaft assembly can be made more precise and small, and the tensile fracture strength of the shaft can be guaranteed to meet the requirements of the mobile phone being light and thin. It can also be used in other opening and closing devices, for example, flip-cover electronic devices, such as laptop computers and other structural parts with opening and closing actions.
[0065] The following description will take a foldable screen mobile phone as an example of an electronic device.
[0066] refer to Figure 3 , Figure 3 The structure diagram of the folding screen mobile phone in the embodiment of the present application is shown. Figure 3 (a)~ Figure 3 As shown in (c) in the figure, the folding screen mobile phone 100 includes a shell, a folding screen and a hinge assembly 30.
[0067] Among them, Figure 3 As shown in (c) in the figure, the housing includes a first frame body 11 and a second frame body 12. The folding screen includes a first screen 21 and a second screen 22, wherein the first screen 21 is disposed on the first frame body 11, and the second screen 22 is disposed on the second frame body 12. The rotating shaft assembly 30 is disposed in the housing and fixed on the housing. The two ends of the rotating shaft assembly 30 are respectively connected to the first frame body 11 and the second frame body 12. Since the rotating shaft can be opened and closed, the mobile phone screen can be folded by rotating the assembly 30. Figure 3 As shown in (a) of FIG. 1 , the mobile phone is in the unfolded state, and after the rotation of the shaft assembly 30, the mobile phone is in the unfolded state. Figure 3The folding action of (b) in the figure is performed, thereby realizing the rotatable connection between the first screen 21 and the second screen 22. Since the hinge assembly 30 is made of the zirconium-based amorphous alloy material in the above embodiment, the hinge assembly can be made more compact and can ensure the tensile fracture strength and hardness, so that the mobile phone as a whole can be thinner and lighter, and the service life will also be improved.
[0068] It should be noted that the structure of the above electronic device is only an exemplary description. In some embodiments, the hinge assembly may be arranged in the middle of a non-display screen, or one side of the hinge assembly may be connected to a frame on which a display screen is mounted, and the other side may be connected to a mobile phone cover, etc. The present application does not limit the specific application and structure of the hinge assembly.
[0069] According to the foldable electronic device of the embodiment of the present application, since it has a rotating shaft assembly made of the zirconium-based amorphous alloy material of the embodiment of the present application, the foldable electronic device can be both light and thin. In addition, the rotating shaft assembly has a high tensile fracture strength, which can avoid the deformation of the rotating shaft as much as possible, which is conducive to extending the service life of the electronic device.
[0070] In other embodiments of the present application, zirconium-based amorphous alloy materials can also be applied to other electronic devices, not only as a rotating shaft, but also as other components with high tensile fracture strength requirements. Among them, the electronic device can be a mobile phone, or a tablet computer, a mobile phone, an e-reader, a remote control, a personal computer (personal computer, PC), a laptop computer, a personal digital assistant (personal digital assistant, PDA), a vehicle-mounted device, an Internet TV, a wearable device, a television, and other products with a display interface, as well as smart display wearable products such as smart watches and smart bracelets. The embodiments of the present application do not impose any special restrictions on the form of the above-mentioned electronic devices.
[0071] In addition, the alloy steel material of the embodiment of the present application can also be applied to other technical fields, such as photovoltaics, semiconductors, etc., for making other devices, for precision forging dies and plastic molds. The present application does not limit the application fields.
[0072] The preparation method of the zirconium-based amorphous alloy material according to the embodiment of the present application is described below with reference to the accompanying drawings.
[0073] refer to Figure 4 , Figure 4 The flowchart of the method for preparing the zirconium-based amorphous alloy material according to the embodiment of the present application is shown. Figure 4 As shown, the method includes S410 - S430 as explained below.
[0074] S410, according to Zr a Cub Al c Ni d Nb e The composition of the alloy is obtained by weighing the required metal raw materials Zr, Cu, Ni, Al and Nb.
[0075] Wherein, a, b, c, d, e are percentages of the number of atoms, and the percentages of the number of atoms are: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100. The zirconium-based amorphous alloy material adds Nb to the composition of the Zr-Cu-Al-Ni alloy, and adjusts the content of each component. The amorphous alloy material with this component content not only has good glass forming ability, but also has high tensile fracture strength.
[0076] In some embodiments of the present application, in the zirconium-based amorphous alloy material composition, the atomic percentage of each element may be 46≤a≤49, 30≤b≤33, 9≤c≤11, 6≤d≤10, 0.5≤e≤5. This component content has higher tensile properties.
[0077] In some embodiments of the present application, the composition of the zirconium-based amorphous alloy material may be: Zr 48 Cu 32 Al 10 Ni7Nb3、Zr 47 Cu 31 Al 10 Ni7Nb5, or Zr 48 Cu 32 Al 10 Ni9Nb1. The amorphous alloy material with this component content has high tensile fracture strength and high Vickers hardness, which can better meet user needs.
[0078] S420, all raw materials are smelted to obtain a master alloy ingot.
[0079] In an embodiment of the present application, each high-purity metal raw material in S410 can be prepared into a master alloy ingot by arc melting under argon protection. In order to ensure that the composition of the alloy ingot is uniform, the alloy ingot is refining at least four times. In some embodiments, the number of refining of the alloy ingot can be increased or decreased according to the content of each raw material component. For example, when the content component is high, it can be increased to 8 or 9 times to achieve uniform composition of the alloy ingot.
[0080] S430, remelting and casting the master alloy ingot to obtain a zirconium-based amorphous alloy material.
[0081] In some embodiments of the present application, the master alloy ingot can be remelted and poured into a 6mm inner diameter copper mold. The melting temperature is 1200-1500°C, for example, 1300°C, 1400°C, etc., and the melting time is 2-4 minutes, for example, 3 minutes. The specific process parameters of copper mold casting can be: vacuum degree is 10 -3 ~10 -2 Pa, for example, can be 10 -3 Pa, 3×10 -3 Pa or 8×10 -3 Pa, etc. The temperature may be 800 to 1400°C, for example, 900°C, 1000°C, 1100°C, 1200°C or 1300°C, etc. The cooling rate may be 10 to 10 2 K / s, for example, 20K / s, 30K / s, 40K / s, 50K / s, 60K / s, 70K / s, 80K / s or 90K / s.
[0082] In some embodiments, the specific process parameters of copper mold casting can be: vacuum degree 5×10 -3 Pa, temperature 1000℃, cooling rate 30K / s. The use of low vacuum can ensure that less oxygen enters the alloy and ensure the alloy performance. This parameter combination can obtain a purer amorphous alloy with less oxygen content and less inclusions.
[0083] In some embodiments of the present application, in step S430, when the master alloy ingot is remelted, the stacking order of the metal raw materials can be Nb, Zr, Ni, Cu, and Al stacked in the vacuum arc melting furnace in descending order of melting point. Stacking according to the melting points of the metals can ensure sufficient melting of the five metals.
[0084] In some embodiments, the mold for remelting and pouring the master alloy is a water-cooled copper mold.
[0085] The preparation method of the zirconium-based amorphous alloy material in the embodiment of the present application, in order to improve the tensile fracture strength of the zirconium-based amorphous alloy material, on the basis of the composition of the Zr-Cu-Al-Ni alloy, by adding the Nb element, and then optimizing the proportion of each element by alloying, to produce the effect of liquid phase separation. It is beneficial to the proliferation and dispersion of the shear band of the zirconium-based amorphous alloy during the stretching process, and avoids the unstable fracture caused by stress concentration. The master alloy ingot is prepared by the arc melting method, and then the zirconium-based amorphous alloy rod is prepared by the copper mold casting method. The zirconium-based amorphous alloy rod has high tensile fracture strength and Vickers hardness. The tensile fracture strength can reach more than 1.8GPa, and the Vickers hardness can reach more than 520HV.
[0086] In addition, the preparation method and preparation process of the embodiment of the present application facilitate the amorphous alloy material to form a good amorphous morphology, and the process is simple and the processing efficiency is high. These high-purity metal raw materials can be produced into bulk materials or products, such as amorphous rods, parts, etc., by melting and casting, which is convenient for mass production and has good application prospects.
[0087] After the above steps, the zirconium-based amorphous alloy material or zirconium-based amorphous alloy product of the embodiment of the present application is obtained, which has high tensile fracture strength and good amorphous forming ability, is not easy to deform, and is beneficial to prolonging the life of the electronic equipment including it.
[0088] The zirconium-based amorphous alloy material and product prepared by the method of the embodiment of the present application have a high tensile fracture strength, which can reach 1.8 GPa or more; the Vickers hardness can reach 520 HV, which is greatly improved compared to the tensile fracture strength of 1.3 GPa of the amorphous alloy material in the prior art.
[0089] The zirconium-based amorphous alloy material and its preparation method provided in the embodiments of the present application are described below through 5 specific embodiments.
[0090] Example 1
[0091] 1) Weigh the amorphous alloy raw material
[0092] Among them, the zirconium-based amorphous alloy material composition is: Zr 48 Cu 32 Al 10 Ni7Nb3, weigh the metal raw materials Zr, Cu, Ni, Al and Nb.
[0093] 2) Melting
[0094] After the high-purity metals (Zr, Cu, Ni, Al, Nb) are prepared according to the atomic percentage, the master alloy ingot is prepared by arc melting under the protection of argon gas, and the alloy ingot is remelted four times. The melting temperature is 1300℃ and the melting time is 3 minutes each time.
[0095] 3) Pouring
[0096] Under high vacuum conditions, the master alloy ingot was remelted and cast into a 6 mm rod-shaped sample, namely, alloy round rod 1, by vacuum casting equipment. The specific process parameters of copper mold casting are as follows: vacuum degree is 5×10 -3 Pa, the temperature is 1000 °C, and the cooling rate is 30 K / s.
[0097] The alloy round rod 1 of the embodiment of the present application is tested and observed below.
[0098] The alloy round rod 1 was subjected to XRD test.
[0099] refer to Figure 5 , Figure 5 The X-ray spectrum of the 6 mm alloy round rod obtained by copper mold casting in Example 1 of the present application is shown. Figure 5 As shown, the results show a "steamed bun-shaped" diffuse scattering peak (no sharp Bragg crystal diffraction peak was observed). The absence of a sharp peak means that no crystalline phase was detected, indicating the completely amorphous structural characteristics of the sample.
[0100] The alloy round rod 1 is processed into a tensile specimen and then subjected to a tensile test.
[0101] refer to Figure 6 , Figure 6 The figure shows the curve of the 6 mm alloy round bar obtained by copper mold casting in Example 1 of the present application during the stretching. Figure 6 As shown, the test results show that its tensile fracture strength is 1949MPa. The alloy bar is tested with a Vickers hardness tester, and the results show that its hardness is 530-540HV.
[0102] The transmission and energy spectrum results of alloy round rod 1 sample were tested.
[0103] refer to Figure 7 , Figure 7 The transmission and energy spectrum images of the 6 mm alloy round rod cast by copper mold in Example 1 of the present application are shown. Figure 7 As shown, the transmission image and energy spectrum image show the uneven distribution of the internal components of the material, indicating that there is an obvious liquid phase separation phenomenon.
[0104] Example 2
[0105] 1) Weigh the amorphous alloy raw material
[0106] Among them, the zirconium-based amorphous alloy material composition is: Zr 47 Cu 31 Al 10 Ni7Nb5, weigh the metal raw materials Zr, Cu, Ni, Al and Nb.
[0107] 2) Melting
[0108] After the high-purity metals (Zr, Cu, Ni, Al, Nb) are prepared according to the atomic percentage, the master alloy ingot is prepared by arc melting under the protection of argon gas, and the alloy ingot is remelted five times. The melting temperature is 1300℃, and each melting time is 3 minutes.
[0109] 3) Pouring
[0110] Under high vacuum conditions, the master alloy ingot is remelted and cast into a 6 mm rod-shaped sample, namely alloy round rod 2, by vacuum casting equipment. The specific process parameters of copper mold casting are as follows: vacuum degree is 5×10 -3 Pa, the temperature is 1000 °C, and the cooling rate is 30 K / s.
[0111] The alloy round rod 2 of the embodiment of the present application is tested and observed below.
[0112] The alloy rod was subjected to XRD test.
[0113] refer to Figure 8 As shown, Figure 8 The X-ray spectrum of the 6 mm alloy round rod cast by copper mold in Example 2 of the present application is shown. Figure 8 As shown, the results show a "steamed bun-shaped" diffuse scattering peak (no sharp Bragg crystal diffraction peak was observed), indicating the completely amorphous structural characteristics of the sample.
[0114] The bars are processed into tensile specimens and then subjected to tensile tests.
[0115] refer to Fig. 9 As shown, Fig. 9 The curve of the 6 mm alloy round rod obtained by copper mold casting in Example 2 of the present application when stretched is shown. Fig. 9 As shown, the test results show that its tensile fracture strength is 1855MPa. The alloy bar is tested with a Vickers hardness tester, and the results show that its hardness is 520-530HV.
[0116] Example 3
[0117] 1) Weigh the amorphous alloy raw material
[0118] Among them, the zirconium-based amorphous alloy material composition is: Zr 48 Cu 32 Al 10 Ni9Nb1, weigh the metal raw materials Zr, Cu, Ni, Al and Nb.
[0119] 2) Melting
[0120] After the high-purity metals (Zr, Cu, Ni, Al, Nb) are prepared according to the atomic percentage, the master alloy ingot is prepared by arc melting under the protection of argon gas, and the alloy ingot is remelted five times. The melting temperature is 1500℃, and each melting time is 2 minutes.
[0121] 3) Pouring
[0122] Under high vacuum conditions, the master alloy ingot is remelted and cast into a 6 mm rod-shaped sample, namely alloy round rod 3, by vacuum casting equipment. The specific process parameters of copper mold casting are as follows: vacuum degree 5×10 -3Pa, temperature 1000 °C, cooling rate 30 K / s.
[0123] The alloy round rod 3 of the embodiment of the present application was tested and observed below.
[0124] The alloy round rod 3 was subjected to XRD test.
[0125] refer to Fig.10 As shown, Fig.10 The X-ray spectrum of the 6 mm alloy round rod obtained by copper mold casting in Example 3 of the present application is shown. Fig.10 As shown, the results show a "steamed bun-shaped" diffuse scattering peak (no sharp Bragg crystal diffraction peak was observed), indicating the completely amorphous structural characteristics of the sample.
[0126] The bars are processed into tensile specimens and then subjected to tensile tests.
[0127] refer to Fig.11 As shown, Fig.11 The curve of the 6 mm alloy round rod obtained by copper mold casting in Example 3 of the present application when stretched is shown. Fig.11 As shown, the test results show that its tensile fracture strength is 1918MPa. The alloy bar is tested with a Vickers hardness tester, and the results show that its hardness is 530-540HV.
[0128] Example 4
[0129] 1) Weigh the amorphous alloy raw material
[0130] Among them, the zirconium-based amorphous alloy material composition is: Zr 53 Cu 20 Al 15 Ni 10 Nb2, weigh the metal raw materials Zr, Cu, Ni, Al and Nb.
[0131] 2) Melting
[0132] After the high-purity metals (Zr, Cu, Ni, Al, Nb) are prepared according to the atomic percentage, the master alloy ingot is prepared by arc melting under the protection of argon gas, and the alloy ingot is remelted six times. The melting temperature is 1200℃ and each melting time is 4 minutes.
[0133] 3) Pouring
[0134] Under high vacuum conditions, the master alloy ingot is remelted and cast into a 6 mm rod-shaped sample, namely, alloy round rod 4, by vacuum casting equipment. The specific process parameters of copper mold casting are as follows: vacuum degree is 10 -2 Pa, the temperature is 800 °C, and the cooling rate is 50 K / s.
[0135] The alloy round rod 4 of the embodiment of the present application is tested and observed below.
[0136] The alloy round rod 4 was subjected to XRD test.
[0137] refer to Fig.12 As shown, Fig.12 The X-ray spectrum of the 6 mm alloy round rod obtained by copper mold casting in Example 4 of the present application is shown. Fig.12 As shown, the results show a "steamed bun-shaped" diffuse scattering peak (no sharp Bragg crystal diffraction peak was observed), indicating the completely amorphous structural characteristics of the sample.
[0138] The bars are processed into tensile specimens and then subjected to tensile tests.
[0139] refer to Fig.13 As shown, Fig.13 The curve of the 6 mm alloy round rod obtained by copper mold casting in Example 4 of the present application when stretched is shown. Fig.13 As shown, the test results show that its tensile fracture strength is 1930MPa. The alloy bar is tested with a Vickers hardness tester, and the results show that its hardness is 528-540HV.
[0140] Example 5
[0141] 1) Weigh the amorphous alloy raw material
[0142] Among them, the zirconium-based amorphous alloy material composition is: Zr 45 Cu 40 Al5Ni8Nb2, weigh the metal raw materials Zr, Cu, Ni, Al and Nb.
[0143] 2) Melting
[0144] After the high-purity metals (Zr, Cu, Ni, Al, Nb) are prepared according to the atomic percentage, the master alloy ingot is prepared by arc melting under the protection of argon gas, and the alloy ingot is remelted four times. The melting temperature is 1300℃, and each melting time is 3min.
[0145] 3) Pouring
[0146] Under high vacuum conditions, the master alloy ingot is remelted and cast into a 6 mm rod-shaped sample, namely alloy round rod 5, by vacuum casting equipment. The specific process parameters of copper mold casting are as follows: vacuum degree is 10 -3 Pa, the temperature is 1400 °C, and the cooling rate is 100 K / s.
[0147] The alloy round rod 5 of the embodiment of the present application is tested and observed below.
[0148] The alloy round rod 5 was subjected to XRD test.
[0149] refer to Fig.14 As shown, Fig.14 The X-ray spectrum of the 6 mm alloy round rod obtained by copper mold casting in Example 5 of the present application is shown. Fig.14 As shown, the results show a "steamed bun-shaped" diffuse scattering peak (no sharp Bragg crystal diffraction peak was observed), indicating the completely amorphous structural characteristics of the sample.
[0150] The bars are processed into tensile specimens and then subjected to tensile tests.
[0151] refer to Fig.15 As shown, Fig.15 The curve of the 6 mm alloy round rod obtained by copper mold casting in Example 5 of the present application when stretched is shown. Fig.15 As shown, the test results show that its tensile fracture strength is 1870MPa. The alloy bar is tested with a Vickers hardness tester, and the results show that its hardness is 522-533HV.
[0152] It can be seen from the results of the embodiments that all the embodiments achieve ultra-high tensile fracture strength while ensuring that the 6 mm alloy rod is amorphous. Combined with the transmission results, it shows that the reason why the embodiments can achieve ultra-high tensile fracture strength is that liquid phase separation occurs, and then there is an uneven distribution of components inside different amorphous phases.
[0153] In summary, the present invention provides a zirconium-based amorphous alloy material with ultra-high tensile fracture strength and a preparation method thereof, by adding Nb element and optimizing the ratio of each component element, so as to produce a liquid phase separation effect. This liquid phase separation effect is conducive to the proliferation and dispersion of shear bands in the zirconium-based amorphous alloy material during the stretching process, and can avoid stress concentration and unstable fracture.
[0154] It should be noted that the materials, equipment and steps are not mentioned in the preparation method of the alloy steel material in the embodiment of the present application. The implementation method of the prior art can be referred to and will not be described in detail here.
[0155] Although the present application has been illustrated and described with reference to certain preferred embodiments thereof, it will be apparent to those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the present application.
Claims
1. A zirconium-based amorphous alloy material, characterized in that: The zirconium-based amorphous alloy material is composed of: Zr a Cu b Al c Ni d Nb e , where a, b, c, d, and e are percentages of the number of atoms, and the percentages of the number of atoms are: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100.
2. The zirconium-based amorphous alloy material according to claim 1, characterized in that: The percentage of each atomic number is: 46≤a≤49, 30≤b≤33, 9≤c≤11, 6≤d≤10, 0.5≤e≤5.
3. The zirconium-based amorphous alloy material according to claim 2, characterized in that: The zirconium-based amorphous alloy material is composed of: Zr 48 Cu 32 Al 10 Ni7Nb3、Zr 48 Cu 32 Al 10 Ni9Nb1 or Zr 53 Cu 20 Al 15 Ni 10 Nb2.
4. The zirconium-based amorphous alloy material according to claim 1, characterized in that: The critical forming size of the zirconium-based amorphous alloy is not less than 6 mm.
5. The zirconium-based amorphous alloy material according to claim 1, characterized in that: The zirconium-based amorphous alloy material has a tensile fracture strength of ≥1.8 GPa and a Vickers hardness of ≥520 HV.
6. A method for preparing a zirconium-based amorphous alloy material, characterized in that: The steps include: According to Zr a Cu b Al c Ni d Nb e The composition of the present invention is to weigh the required metal raw materials Zr, Cu, Ni, Al and Nb, wherein a, b, c, d and e are atomic percentages, and the percentage of each atom is: 41≤a≤60, 18≤b≤50, 4≤c≤17, 4≤d≤12, 0.5≤e≤5, and a+b+c+d+e=100; All raw materials are smelted to obtain a master alloy ingot; The master alloy ingot is remelted and cast to obtain a zirconium-based amorphous alloy material.
7. The preparation method according to claim 6, characterized in that: All raw materials are smelted to obtain a master alloy ingot, including: All raw materials are placed in a vacuum arc melting furnace and melted under argon protection to obtain the master alloy ingot.
8. The preparation method according to claim 7, characterized in that: The metal raw materials Nb, Zr, Ni, Cu and Al are sequentially stacked in the vacuum arc melting furnace in the order of melting points from high to low, and then argon gas is introduced for melting to obtain the master alloy ingot.
9. The preparation method according to claim 8, characterized in that: In the preparation steps of the master alloy ingot, the smelting conditions are: the smelting temperature is 1200-1500° C., and the smelting time each time is 2-4 minutes.
10. The preparation method according to any one of claims 6 to 8, characterized in that: The master alloy ingot is re-refined at least four times.
11. The preparation method according to claim 10, characterized in that: The mold used in the casting is a water-cooled copper mold.
12. The preparation method according to claim 10, characterized in that: Among the pouring process parameters, the vacuum degree is 10 -3 ~10 -2 Pa, temperature is 800~1400℃, cooling rate is 10~10 2 K / s.
13. A rotating shaft assembly, characterized in that: The shaft assembly is made of the zirconium-based amorphous alloy material as described in any one of claims 1 to 5 or the zirconium-based amorphous alloy material obtained according to the preparation method described in claims 6 to 12.
14. An electronic device, characterized in that: include: The housing comprises a first frame and a second frame. A folding screen, the folding screen comprising a first screen and a second screen, the first screen being arranged on the first frame, and the second screen being arranged on the second frame; A shaft assembly, wherein the shaft assembly is disposed in the shell, and the two ends are respectively connected to the first frame and the second frame, and is used to enable the first screen and the second screen to be rotatably connected. The shaft assembly is the shaft assembly described in claim 13.